In vitro validation of a non-invasive continuous blood pressure measurement method for the perioperative application - Geus, Paul; Laidig, Daniel; Borchers, Patrick; Seel, Thomas; Stettin, Johanna; Kertzscher, Ulrich (Current Directions in Biomedical Engineering, 2021)
Hypotensive periods during surgery lead to an increase in postoperative complications. To further avoid the adverse events associated with the invasive measurement of the blood pressure, a perioperative, continuous, non-invasive blood pressure measurement method was developed. The precision of the method was tested for different mean pressure values and different thicknesses of the tissue model using a specifically designed and validated simulator that has the characteristics of the lower arm. The mean pressure difference between the pressure determined by the proposed method and simulated blood pressure from the simulator was 3.93 mmHg (±4.75 mmHg) for the systole and 4.89 mmHg (±6.10 mmHg) for the diastole. The results showed that the method can be a promising alternative to invasive blood pressure measurement methods.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Blood Pressure Measurement; Iterative Learning Control; Non-invasive; Perioperative